Information Security: Modern Realities - Abdugafforovich, Abdullaev Sharof (Journal of Higher Education and Academic Advancement, 2024)
The article discusses the concept of information security, its general meaning, ways to strengthen it, considers ways to protect personal data, considers the concept of information security. Some advice is given to ordinary users.